RANCANGAN QANUN HUKUM KELUARGA ACEH DALAM HIRARKI PERUNDANG-UNDANGAN INDONESIA - Fadli, Fadli; Muammar, Muammar (JURNAL AL-IJTIMAIYYAH, 2019)
This study wants to analyze the position of the Aceh qanun in the Indonesian legislative hierarchy. The discussion on the development of qanun cannot be separated from the events of the 1998 Reformation, which demanded the existence of democracy in various sectors of state life. The implementation of Islamic sharia in Aceh which is carried out by forming qanun-qanun is organized based on the Law on special autonomy, namely Law Number. 8 of 2001 concerning Special Autonomy for the Province of Aceh as the Province of Nanggroe Aceh Darussalam and Law Number. 11 of 2006 concerning Aceh Government. The author analyzes the legality of the Family Law Qanun Draft with the construction of constitutional law in terms of two points of view, namely the formality of establishing legislation and the concept of a unitary state. Based on the background that has been elaborated above, the issues to be discussed are: (1) how is the legality of the Family Law Qanun Draft in terms of the concept of a unitary state? (2) how is the legality of the Family Law Qanun Draft in terms of the formality of forming legislation? The position of Qanun in the legal system in Indonesia is different from local regulations in Indonesia which are also based on several reasons. First, legally the position of Qanun in Aceh Province clearly has a stronger legal force compared to other regional regulations in Indonesia. Secondly, sociologically, the majority of Indonesian population, especially in Aceh Province, implies that they have practiced Islam in their daily lives. Although the level of acceptance of Islamic law itself is stratified, nevertheless Islam becomes the dominant value in daily life, both in the spiritual content, language, culture, practice of behavior to the implementation of Islamic Sharia itself. Third, in terms of Islamic law, the content is loaded with the theme of justice. Islam which in its teachings also contains legal rules is a teaching system as well as a methodology for its achievement, because every nation has the same and universal ideals, in the form of justice, order, peace, harmony, holiness, and so forth. This rule is of course in accordance with the needs of humans who live on this earth.Keywords: Qanun, Family Law, Legislation.